-2(2-4b)=16+3b

Simple and best practice solution for -2(2-4b)=16+3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2-4b)=16+3b equation:


Simplifying
-2(2 + -4b) = 16 + 3b
(2 * -2 + -4b * -2) = 16 + 3b
(-4 + 8b) = 16 + 3b

Solving
-4 + 8b = 16 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-4 + 8b + -3b = 16 + 3b + -3b

Combine like terms: 8b + -3b = 5b
-4 + 5b = 16 + 3b + -3b

Combine like terms: 3b + -3b = 0
-4 + 5b = 16 + 0
-4 + 5b = 16

Add '4' to each side of the equation.
-4 + 4 + 5b = 16 + 4

Combine like terms: -4 + 4 = 0
0 + 5b = 16 + 4
5b = 16 + 4

Combine like terms: 16 + 4 = 20
5b = 20

Divide each side by '5'.
b = 4

Simplifying
b = 4

See similar equations:

| 20w-18=15w+90 | | tanx=2.75 | | 1(j+1)=5(j-3) | | 5/3*-10/9 | | 3(x-5)2=9 | | 6.5+k=17 | | 7x-3=61 | | 1=2x+2x-3 | | 4/7x21 | | 7k+26=25 | | (-6x)-(32)=2x | | x-7/5=2/3 | | hx=x^2+3x-7 | | q+(-23)=-3 | | -6x-(32)=2x | | -18=-6(r-90) | | -3-1/5x=7 | | 5.4+n=10 | | (4)2-4(-5)-1= | | 38=6x+2x-2 | | p/3-12=0 | | m-4/5=1/5 | | (x^2/2r^3)^5 | | 2(x-9)=4(x+-5) | | 72=6(v+5) | | -175=5(4v-7) | | 67=3z-32 | | 28+2w=5(5w+1) | | 3(q-7)=12 | | Y=5z+38 | | 4(-192/x^2)=0 | | (8x-5)+(2x+15)=180 |

Equations solver categories